Monitoring stability of nonconformities per unit with efficient memory-type structure - Hafeez, Waqar; Abbas, Zameer; Nazir, Hafiz Zafar; Sultan, Sajid (Penerbit Universiti Kebangsaan Malaysia, 2025)
For monitoring the qualitative characteristics of interest attribute control charts are recommended. Poisson control charts are most frequently used to track the number of nonconformities per unit in industrial processes during the inspection. This study introduces a Poisson EWMA (PEWMA) charting scheme using a progressive paradigm (PEWMA-p) to improve the sensitivity of the PEWMA chart for possible combinations of smoothing parameters. The proposed PEWMA-p chart has been developed for Poisson processes to monitor nonconformities per unit. The run-length (RL) profiles of the proposed PEWMA-p chart have been computed using extensively applied Monte Carlo simulations. The proposed PEWMA-p chart super-passes the counterparts for monitoring small shifts. An illustrative implementation related to the food quality for the proposed PEWMA-p with existing competitors is also part of the study which highlights the importance of the proposed chart.